Model Peningkatan Kapasitas Financial Komunitas di Kelurahan Cigugur Tengah Cimahi Jawa Barat - Winaktoe, Wied Wiwoho; Irawati, Miya (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2009)
Kelurahan Cigugur Tengah is located at rapidly urbanizing city of Cimahi, West java. This area beared high-rate of population growth (2% per year), 100% Building Coverage Ratio (BCR), and low enviromental quality. This reseach is conducted ar RT 05 the most desified settlement within Kelurahan Cigugur Tengah. Enviromental and settlement quality improvement colud be achieve through redesigning this area towards a integrated form of landuse, environmental, conservation and economic development.